Accumulation of dipeptide repeat proteins predates that of TDP‐43 in frontotemporal lobar degeneration associated with hexanucleotide repeat expansions in C9ORF72 gene. (30th April 2015) - Baborie, Atik; Griffiths, Timothy D.; Jaros, Evelyn; Perry, Robert; McKeith, Ian G.; Burn, David J.; Masuda‐Suzukake, Masami; Hasegawa, Masato; Rollinson, Sara; Pickering‐Brown, Stuart; Robinson, Andrew C.; Davidson, Yvonne S.; et al.
<x xml:space="preserve">Abstract</x> Aims Frontotemporal lobar degeneration (FTLD) and motor neurone disease are linked by the possession of a hexanucleotide repeat expansion in C9ORF72, and both show neuronal cytoplasmic inclusions within cerebellar and hippocampal neurones which are TDP‐43 negative but immunoreactive for p62 and dipeptide repeat proteins (DPR), these being generated by a non‐ATG RAN translation of the expanded region of the gene. Methods Twenty‐two cases of FTLD from Newcastle were analysed for an expansion in C9ORF72 by repeat primed PCR and Southern blot. Detailed case note analysis was performed, and blinded retrospective clinical impressions were achieved by review of clinical histories. Sections from all major brain regions were immunostained for TDP‐43, p62 and DPR. The extent of TDP‐43 and DPR pathology in expansion bearers was compared with that in 13 other previously identified cases from the Manchester Brain Bank with established disease. Results Three Newcastle patients bearing an expansion in C9ORF72 were identified. These three patients died prematurely, two from bronchopneumonia within 10 months and 3 years of onset, and one from myocardial infarction 3 years after onset. In all three, DPR were plentiful throughout all cerebral cortical regions, hippocampus and cerebellum, but TDP‐43 pathological changes were sparse. The severity of DPR pathological changes in these three patients was similar to that in the Manchester series, although the extent of TDP‐43 pathology was significantly less. Conclusion Widespread accumulation of DPR within nerve cells may occur much earlier than that of TDP‐43 in patients with FTLD bearing expansion in C9ORF72.